Traffic Light Management Systems Using Reinforcement Learning - Can, Sultan Kubra; Thahir, Adam Rizvi; Cos¸kun, Mustafa; Güngör, Vehbi Çağrı; Coskun, Mustafa (Institute of Electrical and Electronics Engineers Inc., 2022)
While reducing traffic congestion and decrease the number of traffic accidents in the intersections, most of the traffic light management approaches cannot adapt well to fast changing traffic dynamics and growing demands of the intersections with modern world developments. To overcome this problem, adaptive traffic controllers are developed, and detectors and sensors are added to systems to enable adoption and dynamism. Recently, reinforcement learning has shown its capability to learn the dynamics of complex environments, such as urban traffic. Although it was studied in single junction systems, one of the problems was the lack of consistency with how the real world system works. Most of the systems assume that the environment is fully observable or actions would be freely executed using simulators. This study aims to merge usefulness of reinforcement learning methods with real-world traffic constraints. Comparative performance evaluations show that the reinforcement learning algorithm (Advantage Actor-Critic (A2C)) converges well while staying stable under changing traffic dynamics. © 2022 Elsevier B.V., All rights reserved.
Keywords: Reinforcement Learning; Traffic Light Management; Adaptive Control Systems; Dynamics; Intelligent Systems; Learning Algorithms; Learning Systems; Street Traffic Control; Traffic Congestion; Complex Environments; Dynamic Demand; Growing Demand; Learn+; Management Systems; Reinforcement Learnings; Traffic Controllers; Traffic Dynamics; Traffic Light Managements; Urban Traffic; Reinforcement Learning